Efeito vasorrelaxante do óleo essencial de Lippia microphylla Cham. e seus constituintes majoritários em artéria pulmonar de rato: mecanismo de ação do timol - Sampaio, Renata de Souza Sampaio (2017)
The species Lippia microphylla Cham. has been described in Guyana and in Brazil, popularly known as “alecrim-do-mato”, “alecrim-de-tabuleiro” and “alecrim-pimenta”, used by the population as an antiseptic or in the treatment of respiratory diseases such as colds, flu, bronchitis, cough and asthma. The essential oil of this species (LM-OE) has as major compounds the monoterpenes isomers of position thymol and carvacrol, where several pharmacological activities have already been described for these compounds. Therefore, the objective of this study was to evaluate the vasodilatory effect of LM-OE and its major components in the pulmonary artery (AP) of the rat. All experimental protocols were approved by CEUA / UFPB (certificate: 0501/13). It was observed that LM-OE, thymol and carvacrol relaxed the pulmonary artery of the rat when contracted with FEN in the absence (EC50 = 21,83 ± 1,9 μg/mL, EC50 = 23,02 ± 3,8 μg/mL, EC50 = 15,8 ± 1,0 μg/mL, respectively) as in the presence (EC50 = 29,1 ± 5 μg/mL, EC50 = 6,6 ± 0,9 μg/mL, EC50 = 20,4 ± 4,2 μg/mL) of the functional endothelium; Presence of the endothelium was more potent in relaxing the PA, so we decided to investigate the mechanism of action of this compound in this condition. Activation of endothelial muscarinic receptors is one of the main smooth muscle relaxation pathways, since this activation will induce eNOS activation and nitric oxide (NO) production. For this, atropine, an antagonist of these receptors, was used. The results showed that the relaxing potency was reduced by approximately 4 times in the presence of the blocker (EC50 = 27,1 ± 3,7 μg/mL). We then evaluated whether the thymol was positively modulating eNOS to exert its vasorelaxant effect, for which the L-NAME was used as a selective inhibitor of this enzyme. It was observed that in the presence of this blocker the thymol relaxing potency was reduced by approximately 2-fold (EC50 = 14,7 ± 1,2 μg/mL). Considering this, we investigated the participation of another important endothelial-derived relaxing factor, prostacyclins (PGI2), in the thymol relaxing effect, for that it was used Indomethacin, which is a COX blocker, is the enzyme responsible for the production of PGI2. It was evidenced that the thymol relaxing potency was reduced by about 4 times (EC 50 = 27.7 ± 2.6 μg / mL). As indomethacin was more effective in inhibiting the vasorelexing effect of thymol when compared to L-NAME, we decided to further investigate the PGI2 pathway. The PGI2 receptor in AP smooth muscle is coupled to GS which in turn will activate the adenylyl (AC) cyclase, on which we use the IPA, AC blocker. It was possible to observe that in the presence of the blocker the thymol relaxing potency was about 3 times lower (EC50 = 18,0 ± 1,0 μg/mL). Following the pathway, the next step was to investigate whether thymol would be positively modulating PKA to exert its vasorelaxant effect, for which H-89, an inhibitor of this protein, was used. In the results we can observe that thymol was about 2-fold lower in the presence of H-89 (EC50 = 13,7 ± 1,3 μg/mL). As the mechanism of smooth muscle contraction involves the participation of the K+ and Ca2+ ions, we were able to evaluate if the thymol is acting in the channels of these ions to exert their relaxing effect. For this, contractions were induced with 30 mM or 80 mM KCl, where no statistical differences were observed between the two conditions (EC50 = 18,6 ± 3,4 e 15,1 ± 2,2 μg/mL, respectively). Indicating that the compound would be acting in a common post to the pathway, voltage-activated Ca2+ channels (CaV). To confirm this hypothesis, cumulative concentration-response curves were made to CaCl2 in nominally non-Ca2+ depolarizing medium in the absence and presence of thymol, which antagonized these contractions, in addition to relaxing the pre-contracted organ with S-(-)- Bay K 8644 (EC50 = 10,6 ± 2 μg/mL). In addition, the thymol relaxing potency was not altered (10,1 ± 2,1 μg / mL) in the presence of Y-27632, a Rho kinase inhibitor (ROCK). In conclusion, thymol acts by modulating positively the endothelial muscarinic receptors, eNOS and the PGI2-AC-PKA pathway, in addition to inhibiting CaV1 to exert their relaxing effect on the pulmonary artery of the rat.